Барклай иль Кутузов [Barclay or Kutuzov] - Gabriel Superfin (Slavica Revalensia)
This article points to a likely subtext of one of the passages in Joseph Stalin’s article “Otvet tovarishchu Razinu” (1947)—a private letter from Nikolai Bukharin to Stalin dated December 10th, 1937. It is possible that the doomed Bukharin’s letter, in which he compared himself to Michael Andreas Barclay de Tolly, infuriated Stalin to such an extent that he alluded to this text in his article written almost ten years after Bukharin’s execution, and published “Otvet tovarishchu Razinu” on the tenth anniversary of Bukharin’s arrest.